Exploring demographic and socioeconomic drivers of food insecurity in Colombian households (2023)
Attaining the Sustainable Development Goal of eradicating hunger and reducing moderate to severe food insecurity by 2030 is imperative. According to FAO, global moderate or severe food insecurity have risen over six years, affecting over 30% of the world's population. In 2020, Latin America experienced a substantial increase, with a nine-point rise in food insecurity. In Colombia, data from the latest National Nutritional Situation Survey (ENSIN) of 2015 revealed that 54.2 out of 100 households faced food insecurity. This study investigated the demographic and socio-economic factors contributing to food insecurity in Colombian households, utilizing ENSIN 2015 microdata and the Latin American and Caribbean Household Food Security Measurement Scale (ELCSA). Employing Binary Logistic Model (BLM) and Ordered Logistic Model (OLM), age was identified as a protective factor, decreasing the likelihood of food insecurity. Female-headed households, indigenous or Afro-Colombian identities, urban locations, regional disparities, wealth inequalities, unemployment, and lower educational attainment consistently correlated with a higher likelihood of food insecurity. This research, relevant for evidence-based policy formulation underscores the urgent need to understand household-level food insecurity for the effective design of targeted interventions.